Eugene Alfred Forsey, 1904-1991: Caring Canadian - Cherwinski, W. J. C. (Walter Joseph Carl) (Labour / Le Travail, 1991)
Pays homage to the life and work of Eugene Forsey, who for many years was the research director of the Canadian Congress of Labour/Canadian Labour Congress and later was appointed a senator by prime minister Pierre Elliott Trudeau. An influential advocate of the study of labour history, Forsey's book, "Trade Unions in Canada, 1812-1902," a standard reference work in the field, was the fruit of a CLC project of the 1960s, for which Canada Council funding was obtained to hire graduate students to assist with the research. Forsey also helped to obtain funding for the founding of the journal, Labour/Le Travail. A photo of Forsey is included.
Keywords: FORSEY; Eugene Alfred; 1904-1991; Obituaries